Intensification of the Process of Drying Fruits and Vegetables in a Recirculating Solar Dryer - M.R., Nazarov; N.M., Nazarova; B.Kh., Rajabov; Sh.K., Umedov (RA Journal of Applied Research, 2022)
To intensify the drying process and refine the modes of drying fruits and vegetables, the authors have developed a recirculating solar dryer with a recuperative heat exchanger for drying fruit and vegetable products with a loading capacity of 30 kg for fresh fruit. The solar drying plant contains a drying chamber equipped with a ventilation system, an autonomous power supply unit (solar panel), a control panel and automatic control systems. The recirculating solar dryer works only with solar energy. In this solar dryer, the kinetics of fruit drying was studied in the drying agent recirculation mode with and without a heat exchanger. It has been established that in the recirculation mode, the drying time of fruits is reduced by 1.5-2 times compared to that in a conventional solar dryer.